The measurement of household welfare - Blundell, Richard W. 1952-; Preston, Ian 1964-; Walker, Ian 1957- (Cambridge University Press, 1994)
The measurement of household welfare is one of the most compelling yet demanding areas in economics. To place the analysis of inequality and poverty within an economic framework where individuals are making decisions about current and lifetime incomes and expenditures is a difficult task, made all the more challenging by the complexity of the decision-making process in which households are involved and the variety of constraints they face. This 1994 book examines the conceptual and practical difficulties of making inferences from observed behaviour. It addresses the problems of making comparisons across a range of very different households and discusses how data for such comparisons should be collected. The contributions, from experts from Europe, North America and Australia, have the unifying theme that there is a strong relationship between theoretical concepts from microeconomics and the appropriate use of micro data in evaluating household welfare
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Mathematisches Modell; Wirtschaft; Welfare economics / Mathematical models; Households / Economic conditions / Mathematical models; Home economics / Mathematical models; Familie; Wohlstand; Haushalt; Wirtschaftstheorie; Aufsatzsammlung